On the Origin of Rheumatoid Arthritis: The Impact of Environment and Genes—A Population Based Twin Study - Svendsen, Anders J. (Public Library of Science, 2013)
BACKGROUND: Rheumatoid arthritis (RA) is an autoimmune disease with a complex origin. Previous studies have reported heritability estimates on RA at about 60%. Only 16% of the genetic background of the disease has been disclosed so far. The purpose of the present investigation was to provide an optimized estimate on the heritability of RA and to study the recurrence risk in a nationwide Caucasian twin population. METHODS AND FINDINGS: In a mail survey addressed to 56.707 twin individuals, RA was reported by 479 individuals, mean age 52 (range 16–73). Respondents underwent an interview and clinical examination. Ascertainment probability was 80%. RA was confirmed in 162 twin individuals yielding a prevalence at 0.37% (95% CI 0.31–0.43). The mean discordance time was 19 years (range 0–57). The concordance was 9.1% (95% CI 1.9 to 24.3) in MZ, 6.4% (95% CI 2.1 to 14.3) in DZss. The increased relative risk of attracting RA conditioned on having an affected cotwin compared to the background population risk was 24.6 to 35.4 in MZ twins and 17.3 to 31.6 in DZss twins. The correlation coefficients were 0.60 (0.33 to 0.78) in monozygotic (MZ) and 0.55 (0.33 to 0.72) in dizygotic same sexed (DZss) pairs. Twelve percent (95% CI 0–76%) of the phenotypic variance in the liability to RA was due to additive genetic effects, 50% (95% CI 0–72%) to shared environmental effects and 38% (95% CI 17–61%) to non-shared environmental effects. CONCLUSIONS: This study emphasizes that family factors are important for the development of RA. Although genetic effectors are important, shared and non-shared environmental triggers and/or epigenetic stochastic events seem to be even more significant. However, it should be borne in mind that the genetic and non-genetic components may not be the same across disease subsets.